An intelligence based model for the prevention of advanced cyber-attacks - Adebayo, Olawale Surajudeen; Abdul Aziz, Normaziah (IEEE, 2014)
The trend and motive of Cyber-attacks have gone beyond traditional damages and challenges to information stealing for political and economic gain. With the recent APT (Advance Persistent Threat), which comprises of Zero-day malware, Polymorphic malware, and Blended threat, the task of protecting vita infrastructures are increasingly becoming difficult. This paper proposes an intelligence based technique that combined the traditional signature based detection with the next generation based detection. The proposed model consists of virtual execution environment, detection, and prevention module. The virtual execution environment is designated to analyze and execute a suspected file contains malware while other module inspect, detect, and prevent malware execution based on the intelligent gathering in the central management system (CMS). The model based on Next Generation Malware Detection of creating threat intelligence for future occurrence prevention. The new model shall take into consideration lapses and benefits of the existing detectors.